Penerapan Sistem Merit Pada Undang-Undang Nomor 20 Tahun 2023 Tentang Aparatur Sipil Negara Dalam Pengisian Jabatan Oleh TNI - M. Habib Husen (Eastasouth Institute, 2025)
This research is grounded in constitutional and administrative concerns surrounding the appointment of Indonesian National Armed Forces (TNI) personnel to civil service (ASN) positions without the application of a rigorous merit system. This issue generates tension between bureaucratic professionalism, civil–military relations, and the rule-of-law principles that underpin modern public governance. The study employs a normative juridical method, utilizing statutory analysis, doctrinal review, and examination of relevant judicial decisions to assess the compatibility of such appointments with Indonesia’s positive legal framework. The findings reveal that placing active-duty TNI personnel in ASN positions without objective merit-based selection creates structural problems, including weakened bureaucratic neutrality, diminished institutional independence, and increased risk of maladministration due to regulatory disharmony between the ASN Law and the TNI Law. The study concludes that such assignments are only justifiable when they fully comply with merit principles, transparency, accountability, and a clear separation of civil and military functions.